The mitochondrion genome of Heveochlorella roystonensis (Trebouxiophyceae) contains large direct repeats. Issue 2 (2nd April 2020) - Ma, Shuai; Yu, Bohan; Han, Bingying; Tan, Deguan; Fu, Lili; Mu, Yaojia; Sun, Xuepiao; Zhang, Jiaming
Abstract: The mitochondrial genome of the epiphytic green alga, Heveochlorella roystonensis was sequenced and characterized. The complete mitogenome contains 130, 507 bp, including a single-copy region of 54, 865 bp and two direct repeat regions of 37, 816 and 37, 826 bp, respectively, and has a G + C content of 34.2%. It contains 110 genes, including 73 protein coding genes, 34 tRNA, and three rRNA genes. The large direct repeat makes it currently the largest mitochondrial genome in Trebouxiophyceae.